MENILIK METODE TAKHRIJ HADIS MANUAL DAN DIGITAL - Alisa, Nur Alisa; Silondae, Prades Ariato; Sahib, Muhammad Amin; Sakka, Abdul Rahman; Asiah, Nur Asiah (IAIN KENDARI, 2023)
Hadith initially relied solely on the power of memorization of companions and scholars. However, as more and more hadith memorizers became martyred and the fear of the loss of the Prophet's words increased, the codification of hadith books was soon undertaken. After the process of codification of hadith, the next problem is the difficulty of finding the original source of a hadith. The type of research used is descriptive qualitative research using literature study as a method of collecting data. The purpose of this research is to find out the definition, history, process and methods used in conducting hadith research or tracking. The results showed that the method used to find out the location of a hadith in the original book that lists the hadith complete with its sanad and matan is called the hadith takhrij method. This method was initially not really needed by the mutaqaddimin scholars because they had an established knowledge of hadith. The development of increasingly complex Islamic disciplines made it difficult for the later scholars to find the original source of a hadith, so they tried to formulate various methods in order to find hadith quickly and easily. Along with the development of time, hadith takhrij methods can not only be searched through books (manually) but can also be done through applications or digital platforms.